House of Glass : Culture, Modernity, and the State in Southeast Asia - Yao, Souchou (Book collections on Project MUSE., 2001)
Drawing on critical theory and post-modernism, this book argues for a new strategy for writing about the social and cultural experiences of living in modern Southeast Asian states. Contributors -- many of whom work in universities in the region -- question the processes of cultural transformation under conditions of globalization and rapid economic and political change. By paying attention to the specificity of what is taking place in the particular state, the book questions the conventional narratives of developmentalism and state-sponsored national peace as they are understood in Southeast Asia, and shows how such understanding can be made and unmade.